2018
DOI: 10.1002/bsl.2380
|View full text |Cite
|
Sign up to set email alerts
|

Judicial appraisals of risk assessment in sentencing

Abstract: The assessment of an offender's risk of recidivism is emerging as a key consideration in sentencing policy in many US jurisdictions. However, little information is available on how actual sentencing judges view this development. This study surveys the views of a population sample of judges in Virginia, the state that has gone further than any other in legislatively mandating risk assessment for certain drug and property offenders. Results indicate that a strong majority of judges endorse the principle that sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
28
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 17 publications
2
28
1
Order By: Relevance
“…Although the NVRA assigns a determination of low or high risk to an individual convicted of committing certain crimes, judges are ultimately responsible for making the final sentencing determination. A study conducted by Monahan et al (2018) found that a substantial majority of Virginia judges are familiar with the instrument, and usually consider the results when sentencing an individual. Results indicated that judges believe that an individual's risk of recidivating ought to be taken into consideration when determining whether or not alternative sanctions are appropriate (Monahan et al, 2018).…”
Section: Judicial Perceptions Of Risk Assessment In Sentencingmentioning
confidence: 99%
“…Although the NVRA assigns a determination of low or high risk to an individual convicted of committing certain crimes, judges are ultimately responsible for making the final sentencing determination. A study conducted by Monahan et al (2018) found that a substantial majority of Virginia judges are familiar with the instrument, and usually consider the results when sentencing an individual. Results indicated that judges believe that an individual's risk of recidivating ought to be taken into consideration when determining whether or not alternative sanctions are appropriate (Monahan et al, 2018).…”
Section: Judicial Perceptions Of Risk Assessment In Sentencingmentioning
confidence: 99%
“…Several recent studies have investigated public [17,39,43] and practitioner [29,42] perspectives on the use of algorithmic systems in the context of public sector decision making. Scurich and Monahan [39] and Grgić-Hlača et al [17] investigate the narrower question how the inclusion of particular features influences public perceptions of justice and fairness.…”
Section: Background and Motivationmentioning
confidence: 99%
“…In a study of Virginia sentencing, researchers found that eligible offenders did not receive the alternative sentences that the risk assessment recommended. Many judges explained, in responses to a survey by the same research team, that resource constraints limited their ability to follow the risk assessment recommendations (Monahan, Metz, & Garrett, 2018). An analysis of alternative sentencing outcomes confirmed that judges were more likely to divert offenders in districts with greater treatment resources (Garrett, Jakubow & Monahan, 2019).…”
Section: Insufficient Resourcesmentioning
confidence: 99%